2007
DOI: 10.1016/j.dnarep.2007.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Transcription-associated mutagenesis in yeast is directly proportional to the level of gene expression and influenced by the direction of DNA replication

Abstract: A high level of transcription has been associated with elevated spontaneous mutation and recombination rates in eukaryotic organisms. To determine whether the transcription level is directly correlated with the degree of genomic instability, we have developed a tetracycline-regulated LYS2 reporter system to modulate the transcription level over a broad range in Saccharomyces cerevisiae. We find that spontaneous mutation rate is directly proportional to the transcription level, suggesting that movement of RNA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
115
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(128 citation statements)
references
References 44 publications
9
115
1
1
Order By: Relevance
“…We found no genome-wide correlation in mutation rate with local GC content in yeast, suggesting that GC contentrelated effects on substitution rate are largely due to postmutation selection or selection-like processes such as biased gene conversion. Next, we looked at highly transcribed genes that are thought to have elevated mutation rates due to transcription-associated mutagenesis (49)(50)(51)(52). In our data, we found no genome-wide correlation in mutation rate with transcription rate.…”
Section: Discussionmentioning
confidence: 35%
“…We found no genome-wide correlation in mutation rate with local GC content in yeast, suggesting that GC contentrelated effects on substitution rate are largely due to postmutation selection or selection-like processes such as biased gene conversion. Next, we looked at highly transcribed genes that are thought to have elevated mutation rates due to transcription-associated mutagenesis (49)(50)(51)(52). In our data, we found no genome-wide correlation in mutation rate with transcription rate.…”
Section: Discussionmentioning
confidence: 35%
“…Mutagenesis by g-rays and methylmethane sulfonate is also lowered in rev3 mutants [4,10,13], and the frequency of spontaneous point mutations is reduced by at least half [14][15][16]. Spontaneous mutation in S. cerevisiae is proportional to transcription level at some loci, and this transcription-associated mutagenesis is also Rev3-dependent [17]. These results indicate that the majority of mutagenic bypass events in budding yeast involve pol ζ.…”
Section: Dna Pol ζ In Saccharomyces Cerevisiaementioning
confidence: 73%
“…In Saccharomyces cereviseae by genome wide analysis it was shown that replication fork is paused by RNAP II in highly transcribed genes (Azvolinsky et al 2009). Other studies on yeast showed that genome integrity is compromised by impairment of the replisome during head-on collisions with RNAP II which might promote transcription associated recombination (Kim et al 2007;Prado et al 2005). All these findings relate directly to the mechanisms of overcoming obstacles by the two machineries with major emphasis on the outcome of the replisome in terms of its integrity and stability that clearly is affected depending on the directionality of the collisions.…”
Section: The Effects Of Rnap On Replication and Genome Integritymentioning
confidence: 96%